Intentionality, desire, responsibility : a study in phenomenology, psychoanalysis and law - Mooij, Antoine, 1944- (Studies in Contemporary Phenomenology, 2010)
Recently, the predominance of natural sciences seems to have cast doubt on the legitimacy of the human sciences. Adopting a phenomenological and hermeneutical point of view, this book is intended to contribute towards a justification of the human sciences, taking account of quintessentially human characteristics. The basic assumption is that man interprets his own experience and the world around him, yielding to the limitations imposed by language. Central themes are intentionality and causality, desire and lack, responsibility and loss of responsibility. Relevant domains are psychopathology and psychoanalysis-following Lacan's interpretation - and law. The rich phenomenological traditions in these domains will be drawn from throughout this book.